INCIDENCE AND RISK FACTORS OF FEBRILE SEIZURES AT PEDIATRIC DEPARTMENT OF BOLAN MEDICAL COMPLEX HOSPITAL, QUETTA (Journal of Medical & Health Sciences Review, 2025)
Febrile seizures (FS) are common neurological events in children aged 6 months to 5 years, triggered by fever without intracranial infection or metabolic disturbance. This descriptive cross-sectional study assessed the incidence and risk factors of FS among 1120 pediatric patients presenting with seizures at Bolan Medical Complex Hospital, Quetta, Pakistan. The incidence of FS was 6.25%, predominantly affecting males aged 6–36 months. Simple FS accounted for 77.1%, while 22.9% were complex. A significant association was found between cesarean delivery and complex FS (p=0.007). Positive family history of FS or epilepsy was common, although complex FS was more frequent in children without such history. Developmental delays and low Apgar scores were prevalent but not statistically significant risk factors. Hypozincemia and incomplete immunization were also common. These findings highlight the multifactorial etiology of FS and suggest the influence of perinatal and environmental factors, particularly in resource-limited settings. Further multicenter studies are needed to elucidate causality and improve preventive strategies.